Correlation of Non-Compact Myocardial Layer Characteristics With the Risk of Death and Thrombotic Complications in Dilated Phenotype of Non-Compact Myocardium in Children: Cohort Study Results - M. K. Umarova; Ye. N. Basargina; I. V. Silnova (Вопросы современной педиатрии, 2016)
Background: Non-compact myocardium is a form of cardiomyopathy, which is characterized by an abnormal trabecular (non-compact) layer of the ventricular myocardium. The correlation between the severity of a non-compact myocardial layer and peculiarities of course and outcome of the disease remains unclear.Objective: Our aim was to examine the relationship of the ratio value of the non-compact and compact myocardial layer (NC/C) thickness, as well as of the number of non-compact segments of the left ventricle (LV) of the heart with the risk of death and thrombotic complications in children with dilated phenotype of non-compact myocardium.Methods: The results of a prospective cohort study, which included children hospitalized to a specialized hospital from October 2011 to May 2015, are presented. The presence of non-compact myocardium was established on the basis of echocardiography results.Results: The study included 48 children with non-compact myocardium and LV myocardium remodelling on the dilatation phenotype. Fatal outcome in 19 (8; 61) months from the date of detection of heart changes occurred in 11 (23%) cases. The development of thrombotic complications (cardioembolism, intravascular thrombosis before or during the observation) is recorded in 8 (17%) children. The risk of death and thrombotic complications did not depend on the NC/C value and the number of non-compact LV segments.Conclusion: The value of the ratio of NC/C and the number of non-compact LV myocardial segments does not allow to predict the course of the disease in children with dilated phenotype of non-compact myocardium in relation to the development of thrombotic complications and occurrence of fatal outcome.